Study Of Distribution And Level Of Nitrate And Nitrite Dissoalved O2 (DO) Central Estuary Aek Tolang Pandan North Sumatra Province - Eryandi sitanggang; Mubarak '; Rifardi ' (Universitas Riau, 2010)
This research was conducted in May 2009, in the waters of Muara Aek Tolang Pandan Central Tapanuli of North Sumatra Province. The purpose of this study wasto map the distribution pattern of nitrate and nitrite content and O2 content (DO)dissolved in the mouth of the river Aek tolang horizontally. The method used in thisresearch was survey method. The primary data obtained from direct measurementsand sampling directly in the field and then tabulated and analyzed in the laboratoryare discussed further in descriptive, while secondary data related to research obtainedfrom the relevant authorities. spreading pattern of Nitrate and Nitrite concentrationdistribution was influenced by tides and currents. It can be seen by the differences inconcentration at the surface and ground waters at high tide and low tide at the samestation point. At the time of ups and downs have a much different variations on eachstation. The concentration of dissolved O2 measurements conducted at research sitesat high tide waters ranged from 111.6 ppt - 442.3 ppt. Based on measurements takenin Coastal Estuary Aek Tolang Pandan then the quality of waters in the study area nogood.Keywords: Nitrate and nitrite content, O2 content (DO)dissolved, Spreading